Optimizing Community Income through Ponds Catfish Farming in Griya Cendekia UII Sedayu Bantul: Indonesia - Priyadi, Unggul; Hamdani , Rizki; Putri, Alivia Rianti (UII, 2026)
Aquaculture is an important sector that plays a role in supporting food security while improving the economy of rural communities. This activity is an easy alternative because it can utilize limited land and simple media, such as ponds. Bantul Regency is one of the areas in the Special Region of Yogyakarta that has aquaculture activities with promising prospects. Catfish is the favorite fish of the community in terms of consumption, so it is not surprising that the production volume of catfish is quite high on a regional scale. This community service activity aims to encourage and enhance community empowerment in managing vacant land potential so that the community can have additional income through catfish farming using tarpaulin ponds in the Griya Cendekia UII Sedayu Bantul assisted village located in Padukuhan Kaliberot. The results of catfish farming are used as a marketing tool that can improve community welfare and create new jobs. The community service methods implemented include the identification of problems and potential partners; the construction of catfish ponds; training in catfish pond cultivation; program monitoring; and evaluation and sustainability strategies. The results of community service activities show that these activities improve the community's ability to manage catfish productively and optimize marketing management. These activities conclude that catfish farming not only supports the environmental ecosystem but also creates new economic opportunities for the community.